2003
DOI: 10.1002/bjs.4129
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative detection of disseminated tumour cells is an independent prognostic factor in patients with colorectal cancer

Abstract: Disseminated tumour cells detected by CYT and ICC represent an independent prognostic factor in patients undergoing surgery for colorectal cancer and may identify patients at high risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 18 publications
(7 reference statements)
0
28
0
1
Order By: Relevance
“…Eight studies were excluded as they reported only on preoperative blood sampling (Bessa et al, 2001;Fujita et al, 2001;Wong et al, 2001;Zhang et al, 2005;Douard et al, 2006;Iinuma et al, 2006;Wang et al, 2006;Friederichs et al, 2007). Nine studies were excluded as they contained data from which outcomes could not be extracted, of which four were excluded as they combined positive results of molecular detection of multiple samples and their effect on prognosis (Hardingham et al, 2000;Guller et al, 2002;Bosch et al, 2003;Koyanagi et al, 2008), and five were excluded as it was impossible to extract the data for outcomes of interest (White and Griffiths, 1976;Funaki et al, 1998;Wyld et al, 1998;Conzelmann et al, 2005;Wang et al, 2007). Five studies were excluded as they were reviews or systematic reviews, which did not report on prognostic outcomes (Tsavellas et al, 2001;Sleijfer et al, 2007;Riethdorf et al, 2008;Sergeant et al, 2008;Tsouma et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were excluded as they reported only on preoperative blood sampling (Bessa et al, 2001;Fujita et al, 2001;Wong et al, 2001;Zhang et al, 2005;Douard et al, 2006;Iinuma et al, 2006;Wang et al, 2006;Friederichs et al, 2007). Nine studies were excluded as they contained data from which outcomes could not be extracted, of which four were excluded as they combined positive results of molecular detection of multiple samples and their effect on prognosis (Hardingham et al, 2000;Guller et al, 2002;Bosch et al, 2003;Koyanagi et al, 2008), and five were excluded as it was impossible to extract the data for outcomes of interest (White and Griffiths, 1976;Funaki et al, 1998;Wyld et al, 1998;Conzelmann et al, 2005;Wang et al, 2007). Five studies were excluded as they were reviews or systematic reviews, which did not report on prognostic outcomes (Tsavellas et al, 2001;Sleijfer et al, 2007;Riethdorf et al, 2008;Sergeant et al, 2008;Tsouma et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the same group could not ascertain the prognostic significance of postoperative CTC detection [71]. In contrast to this, Bosch et al showed an independent prognostic significance for CTCs in patients undergoing surgery for CRC by using cytology and immunocytochemistry (ICC) [72]. Some years later, Koch et al suggested that detection of CTCs in intraoperatively drawn PB samples may serve as an independent prognostic factor for tumour relapse after potentially curative resection of CRC liver metastases [73].…”
Section: Presence and Clinical Significance Of Ctcs In Pbmentioning
confidence: 97%
“…There is accumulating evidence that presence of exfoliated tumor cells in the peritoneal cavity after surgery for colorectal cancer, which is considered minimal residual disease, might adversely influence relapse free and overall survival [23,24]. Although surgery remains the only curative option for colorectal cancer, operative trauma to peritoneal surfaces and the subsequent wound healing microenvironment may favor tumor development [7,8,11,25].…”
Section: Discussionmentioning
confidence: 99%